State and democracy in ElíasDíaz(From the social and democratic State of Law) (2013)
The State of lawis built as a rationalhistorical processunder constant review andcriticism.The historical evolution ofthe different models that flows through thislegal and politicalformation does not isolatewi thessentialist characters its definition, but incorporatesa tripleprogressive deepening: ethical principlesandmoral prescriptionsthat underliehuman rights andfundamentalfreedoms, asmoraldemocracy, in plural andactive participation aspolitical democracyand in the institutionalization, protection and guarantee of the same,as legal democracy.Thus,universalization ofthe democratizationof public life thatis calledto be realized in thesocial and democratic Stateof law, which is presented as anunfinishedreality to work constantly. The commitment, plural andresponsible participationand solidarity ofcivilsociety, along with the increasing responsibility of legaland politicalinstitutions, give shape to democratic socialism, with which they will be able to achieve the pretended improvementsin terms ofsocial justice and equity.